DETERMINANTS OF ACADEMIC PERFORMANCE OF UNDERGRADUATES OF THE FACULTY OF MANAGEMENT STUDIES AND COMMERCE OF THE UNIVERSITY OF SRI JAYEWARDENEPURA IN SRI LANKA - Fernando, R (PEOPLE: International Journal of Social Sciences, 2017)
The main purpose of this study is to identify the most significant factors influencing the academic performance of the undergraduates of the Faculty. A systematic random sample of two hundred students representing the second, third and the fourth year of student population of the Faculty in the year 2010 were selected. The data was obtained through a structured questionnaire. Descriptive statistics, factor analysis, reliability analysis, correlation analysis and stepwise multiple regression were used for data analysis. It was found that self-determination; time management, English knowledge and students’ attendance on lectures are positively and significantly (at P < 0.001) affecting the academic performance. Among them, self-determination was the most influential factor, which alone explains 46.4 percent of variance in academic performance of the undergraduates. Also the library usage and self-motivation have shown significant (at p < .01) and positive association with academic performance. Further, active learning has also shown significant (at p< 0.05) and positive association with the academic performance. Those variables altogether were found to explain 69 percent of variance in academic performance of the undergraduates. The implication of this study for improving students’ academic performance of the undergraduates of this Faculty is also outlined.